Diversity of Gastropods and Bivalvia Caught By Pemadak in The Intertidal Zone of Serinting Beach, Special Economic Zone Mandalika - Lulu Febrianti; Imam Bachtiar; Karnan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The intertidal area is utilized by coastal communities to collect intertidal biota during low tides, which is called “madak. Madak culture is also practiced by the people of Sumbawa. One of the groups of animals taken during madak are Gastropods and Bivalves from the Phylum Mollusca. Gastropods and Bivalves have many benefits for coastal communities. One of the direct benefits of Gastropods and Bivalves for society is consumption. This research focuses on the diversity that leads to the taxonomy of Gastropods and Bivalves caught by fishmen in the intertidal zone of Serinting Beach.The present study aims to analyze the diversity of Gastropods and Bivalves harvested during madak, to develop identification keys for harvested Gastropods and Bivalves, and to identify the amount of exploitation of Gastropods and Bivalves in madak. This study used a descriptive method of quantitative approach by purchasing Gastropods and Bivalves harvested by 5 madak-women in 5 days convenience (convenience sampling) The results found 5 orders, 11 families, and 28 species from 715 individuals of Gastropoda, while 2 orders, 3 families, and 4 species from 69 individuals of Bivalvia. Madak Gastropods and bivalves were used to develop identification keys. It was estimated that the number of Gastropods exploited was 3.348,4 individuals and bivalves were 351,6 individuals 1 per month.